Pengaruh Gaya Kepemimpinan Demokratis Terhadap Loyalitas Karyawan Tetap Di PT. Sumber Agro Sulawesi (SAS) Sulawesi Barat - Vira Rosari; Megawati; Andi Baso Adil Natsir (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
An organization’s success in achieving its goals is closely tied to the important role of employee loyalty, which is driven in part by democratic leadership styles. This study was designed to examine how democratic leadership styles influence the loyalty of permanent staff at PT. Sumber Agro Sulawesi (SAS) in West Sulawesi. Using a descriptive quantitative method, this research involved the entire population of permanent employees totaling 30 individuals as the sample (saturation sampling). Data collection instruments included questionnaires, interviews, observations, and a literature review, which were subsequently analyzed using a multiple linear regression model. The results of the partial analysis show that the variables of delegation of responsibility and the intensity of interaction with staff do not have a significant impact on loyalty. However, staff involvement in joint decision-making was found to have a positive and highly significant impact. When examined simultaneously, all aspects of democratic leadership contribute significantly to employee loyalty. Thus, corporations need to adopt a more participatory management style particularly in decision-making to optimize employee loyalty